Protective effect of chlorogenic acid on diclofenac-induced oxidative stress and inflammation in the liver of BALB/c mice - Mohamad Hadi Yazdani; Firoozeh Saghaei; Maryam Karimi-Dehkordi (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: Diclofenac, a non-steroidal anti-inflammatory drug, is known to induce liver damage. This study evaluated the protective effects of chlorogenic acid, a plant compound with anti-inflammatory and antioxidant properties, against diclofenac-induced hepatotoxicity in BALB/c mice. Methods: In this experimental study, 42 BALB/c mice were randomly divided into seven groups: control (saline), diclofenac, chlorogenic acid, diclofenac + chlorogenic acid, diclofenac + vitamin E, diclofenac + propylene glycol (the solvent for chlorogenic acid), and a prevention group (chlorogenic acid administered for six days followed by diclofenac on the seventh day). All treatments were conducted over seven days. At the end of the treatment period, gene expression levels of pro-inflammatory factors, including interleukin 1 beta (IL-1β) and tumor necrosis factor alpha (TNF-α), as well as antioxidant enzymes such as catalase and superoxide dismutase, were measured using RT-PCR. Results: Diclofenac significantly increased the gene expression of pro-inflammatory factors (IL-1β and TNF-α) while decreasing the expression of antioxidant enzymes (catalase and superoxide dismutase). Conversely, administration of chlorogenic acid for seven days significantly reduced the gene expression of pro-inflammatory factors and increased the levels of antioxidant enzymes. Conclusion: The findings of this study indicate that chlorogenic acid exhibits antioxidant and anti-inflammatory effects in liver toxicity induced by diclofenac in mice. These effects are comparable to those of vitamin E.